2015
DOI: 10.15835/buasvmcn-vm:10385
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Parainfluenza Type 3 Virus Antigens in Goats

Abstract: Parainfluenza-3 (PI-3) is the most common virus infection of the respiratory tract of sheep and goats throughout the world. The virus belongs to family Paramyxoviridae of order Mononegaviralis, the non-segmented negative single stranded RNA viruses. Often, infection is complicated by coinfection with respiratory bacteria (Mannheimia haemolytica). In this study, detection of PI-3 virus as causative agent of pneumonia in goat kids was investigated.The virus was detected in lung tissues using direct immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In the present study, the histopathological findings in BPI3V-positive pneumonic sheep lungs were similar to those described in pneumonic caprine lungs (Ceribasi et al 2012;Anita et al 2015;Kamdi et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the histopathological findings in BPI3V-positive pneumonic sheep lungs were similar to those described in pneumonic caprine lungs (Ceribasi et al 2012;Anita et al 2015;Kamdi et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Foci of fluorescence were most commonly observed in these sites, indicating that the initial histopathological changes occur in lambs experimentally infected with the PI3 virus (Stevenson and Hore 1970). In previous works, the DFAT has successfully been used as a rapid diagnostic method for the research of PI3V (Gafer et al 2009;Ceribasi et al 2012;Ceribasi et al 2014;Anita et al 2015). These findings are in accordance with those obtained by Ceribasi et al (2014) where it was demonstrated that specific DFAT stainings for viral antigen in the pneumonic cattle lungs were intensively detected in the bronchiolar epithelium and less frequently in the alveolar epithelium as the size ranged from small to large homogeneous granular masses.…”
Section: Discussionmentioning
confidence: 98%
“…Investigations have been carried out with serological tests such as Virus Neutralization Test (VNT), ELISA, Immunofluorescent Antibody (IFA) and Hemagglutination Inhibition (HI) for the prevalence of ruminant RSV and PI-3 agents (Franco et al, 2020;Tiwari et al, 2016). Immunohistochemical (IHC), Immunofluorescence (IF), Direct Fluorescent Antibody Technique, and Electron Microscope methods are currently used in the lung tissue of ruminant animals to show detailed RSV and PI-3 viruses (Aniță et al, 2015;Jarikre and Emikpe, 2017).…”
mentioning
confidence: 99%
“…This non-segmented negative-sense genome single-stranded RNA virus belongs to the Paramyxoviridae family. PIV-3 can cause pneumonia by itself, however more often is it one of the pathogens of the etiological complex which causes enzootic pneumonia (Anita et al 2015). During the infection clinical signs such as nasal and ocular discharge, cough as well as dyspnea in severer cases, usually accompanied by fever and inappetence, have been observed (Contreras-Luna et al 2017).…”
Section: Introductionmentioning
confidence: 99%